Headache, Chiari I malformation and foramen magnum decompression. Issue 6 (December 2018) - Olszewski, Adam M.; Proctor, Mark R.
Abstract : Purpose of review: With increasing use of MRI, more patients are being diagnosed with Chiari I malformation (CM1), many of whom are asymptomatic. When symptoms are present, headache is the most frequent presenting feature, although symptoms can be variable. The purpose of this review is to help primary care clinicians better understand the relationship between an individual's presenting symptoms and the presence of radiographic CM1, and to describe the expected outcomes for patients who undergo decompression surgery. Recent findings: Recent literature has shown that asymptomatic patients with CM1 tend to have a benign natural history. For symptomatic Chiari malformation, headache is the most common presenting symptom and the majority of patients that present with headache will have symptom improvement after foramen magnum decompression. This improvement is most reliable for patients with classic Chiari-type headache, which are described as occipital or cervical and tussive in nature, but has also been shown in patients with atypical headaches who have undergone surgery. Summary: CM1 is a common radiographic finding and associated symptoms can be variable. The relevance of this finding to a particular patient and need for intervention must be made on an individual basis.